What Lies Concealed in the Roots of Cybernetics: The Renewal of Early Greek Thinking of Being as Physis in Martin Heidegger and Edgar Morin. Issue 3 (December 2020) - Dicks, Henry
Abstract : In the Post-War period, cybernetics came to assume the role of unifying ground of science and technology. In doing so, it not only usurped philosophy, but also replaced the basic concepts of philosophy (being, existence, becoming, appearing, etc.) with those of cybernetics (information, communication, control, feedback, etc.). And yet, as both Heidegger and Morin each in their different ways make clear, there lies concealed in the roots of cybernetics the possibility of a renewed thinking of being, and more specifically of being as physis, where physis is understood as self-production. Articulating the parallel thinking of being as physis proposed by Heidegger and Morin, I argue that this articulation makes it possible to overcome the characteristically metaphysical division of being from becoming, appearing, and existing that originated with Parmenides, thus also making possible the emergence of a 'new beginning' capable of overcoming the unprecedented danger to being posed by modern technology. Abstract : Durant la période de l'après-guerre, le domaine de la cybernétique a assumé le rôle d'instance unificatrice entre science et technologie. Ce faisant, la cybernétique a non seulement usurpé le rôle de la philosophie, mais également remplacé les concepts de base de la philosophie (être, existence, devenir, apparaitre, etc.) par les siens (information, communication, contrôle, retour d'information, etc.). Et pourtant, comme Heidegger et Morin, chacun à leur manière, l'affirment clairement, il se cache dans les racines de de la cybernétique la possibilité d'une pensée renouvelée de l'Être, et plus précisément de l'Être en tant que physis, dans laquelle physis est comprise en tant qu'autoproduction. Après avoir exprimé les pensées parallèles d'Heidegger et de Morin à propos de l'Être en tant que physis, j'avance que cette expression rend possible de transcender la division typiquement métaphysique entre Être et devenir, apparaitre, et exister, dont les origines remontent à Parménide, rendant ainsi possible l'émergence d'un « nouveau début » capable de surmonter le danger sans précédent posé par la technologie moderne.